(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Mental health rehabilitation demands a holistic approach that addresses both the psychological and physical aspects of well-being. This article explores the synergistic relationship between physiotherapy and nursing interventions in supporting mental health recovery. Physiotherapy plays a vital role in enhancing mental wellness through tailored exercise programs, relaxation techniques, and mindfulness practices. Similarly, psychiatric nurses provide essential support through therapeutic relationships, holistic care, and psychosocial interventions. By collaborating, physiotherapists and nurses can create integrated care plans that address both physical and mental health goals. This article discusses collaborative assessment methods, joint therapy sessions, and strategies for incorporating physical activity into psychiatric settings. Despite challenges such as stigma and barriers to participation, the integration of physiotherapy and nursing offers promising avenues for promoting mental health rehabilitation. Through case studies and patient testimonials, this article highlights the transformative impact of collaborative care on mental wellness.